2023
DOI: 10.1002/adfm.202303072
|View full text |Cite
|
Sign up to set email alerts
|

Tailoring Interface to Boost the High‐Performance Aqueous Al Ion Batteries

Abstract: Electrolytes are highly important for aqueous Al ion batteries (AAIBs). However, Al metal anode usually has poor reversibility of plating/tripping, resulting in low Coulombic efficiency (CE) and poor cycling stability by using traditional Al ion electrolyte. Herein, a novel type of aqueous Al ion electrolyte with polyethylene glycol (PEG) as the primary skeleton for solvated Al ions is proposed, named as PEG‐Al@H. Outstandingly, an Al electrolyte interface (AEI) is generated on the Al metal surface during galv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 65 publications
(88 reference statements)
0
11
0
Order By: Relevance
“…In addition, the hydrogen evolution process (HER) and the inefficient plating/stripping of Al ions at the Al anode contribute to heightened irreversibility, leading to a shorter cycle life. Consequently, a viable approach to enhancing the performance of EES devices is to focus on preventing side reactions on the Al metal and improving the reversibility of Al ions during the plating/stripping process …”
Section: Resultsmentioning
confidence: 99%
“…In addition, the hydrogen evolution process (HER) and the inefficient plating/stripping of Al ions at the Al anode contribute to heightened irreversibility, leading to a shorter cycle life. Consequently, a viable approach to enhancing the performance of EES devices is to focus on preventing side reactions on the Al metal and improving the reversibility of Al ions during the plating/stripping process …”
Section: Resultsmentioning
confidence: 99%
“…In ionic liquid (IL)-based electrolyte (for example, AlCl 3 /EMIMCl), AlCl 4 – was shown to be responsible for intercalation/deintercalation in the carbon cathode and Al 2 Cl 7 – for aluminum deposition and stripping on the Al anode, respectively, which led to a very fast charging capability . In comparison, Al deposition/stripping has recently been achieved in aqueous Al batteries using various electrolytes. Among them, aluminum triflate (Al­(TfO) 3 ) and aluminum bis (trifluoromethanesulfonyl)­amide electrolytes with a Zn/Al anode and MnO 2 cathode show a storage capacity of >400 mA h g –1 . In the Zn/Al system, the authors argued that alloying of Al with Zn inhibits the alumina passivation layer and therefore can compete with the hydrogen evolution reaction, which leads to a better Al deposition/stripping as well as show a better battery performance . However, recently, using spectroscopic, electrochemical, and theoretical studies, it was shown that in the Al­(TfO) 3 system that the hydrogen evolution reaction hinders the aluminum deposition/stripping and results in the formation of hydrogen bubbles .…”
Section: Introductionmentioning
confidence: 99%
“…Solar energy and wind energy are ubiquitous renewable energies and can be stored in the form of electrochemical energy. Thus, electrochemical energy storage devices are needed to be developed in order to utilize the primary energy extensively . Besides, the rapid development of portable devices and electric vehicles also demand the rechargeable energy storage devices with excellent properties such as fast charge–discharge rate, high energy density, and power density. The supercapacitor is one kind of electrochemical energy storage device relying on the adsorption of ions on electrodes to store electrical energy. Generally, hydrogen ions (H + ) or hydroxyl ions (OH – ) are potential ions for energy storage in supercapacitors because of their extraordinary ionic mobility in aqueous solution.…”
Section: Introductionmentioning
confidence: 99%
“…To break these restrictions, the abundant high-valent metals, such as zinc, magnesium, and aluminum, should be applied and researched in this field. In comparison with monovalent ions, the high-valent ions have the advantages of fast charge-transfer dynamics, high capacity, and power density. For instance, the theoretical specific energy of aluminum is as high as 2980 mA h/g, second only to lithium among the metallic elements. , Thus, it is a promising field to develop electrochemical energy storage devices based on high-valent metals. However, the large size of high-valent metal ions requires the corresponding size of pores in the electrode to accommodate them during the charge process.…”
Section: Introductionmentioning
confidence: 99%